A Cross-sectional study to assess the Level of Utilization of Immediate Postpartum Family Planning among Postnatal women in Lira Regional Referral Hospital. - Obua, Benard; Okori, Felex (Student’s Journal of Health Research Africa, 2022)
Background: Over 214 million women globally have an unmet need for family planning. The majority of these women are in the postpartum period. About 336 mothers per 1000 live births in Uganda die due to pregnancy-related causes most of which are preventable. The use of contraception can prevent unwanted pregnancies and unsafe abortions that normally lead to the loss of lives of these women. Immediate post-partum family planning services need to be emphasized, where these women should leave the hospital with a safe and effective method of contraception in place. Despite the accepted demand for postpartum family planning, many women do not intend to use modern methods of contraception in the immediate postpartum period. Objective; This study aimed to assess the use and perceptions of women on immediate postpartum family planning among postnatal women attending Lira Regional Referral Hospital. Methods: This was a cross-sectional study conducted on 300 conveniently selected postnatal women in LRRH. The data was obtained and entered, cleaned, and analyzed using SPSS version 23. Univariate analysis was done to determine frequencies and percentages of the study variables and bivariate analysis was done using binary logistic regression to determine associations Results: Of a total of 310 postnatal women invited to the study, 300(97%) participated in the study of which 13(4.3%) reported having utilized IPPFP services. Age (p=0.002), Religion, Counseling, and knowledge about IPPFP (p=0.000) respectively were found to be significantly associated with the use of IPPFP. There was also an association between the client’s poor perceptions of the use of IPPF with (P=0.005). Conclusions and recommendations: The IPPFP use among postnatal women attending Lira Regional Referral Hospital is very low (4.3%). Recommendations Therefore, multi-pronged Interventions should be implemented to address the poor perceptions of these postnatal women toward the uptake of IPPFP.